2009
DOI: 10.1586/ers.09.6
|View full text |Cite
|
Sign up to set email alerts
|

MDR-/XDR-TB management: what it was, current standards and what is ahead

Abstract: Despite killing nearly 2 million people every year, TB is arguably the most neglected disease in terms of the funding and research it receives. In many ways, multidrug-resistant TB is a result of this disregard. In high-burden countries, not many improvements have been implemented in the diagnosis and treatment tools of TB since the 1960s. Following this period, fluoroquinolones, developed for other infections, are the only highly active new drugs against TB. Multidrug- and extensively drug-resistant TB is boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
(75 reference statements)
0
28
0
1
Order By: Relevance
“…In a retrospective study in Iran, successful outcome was observed in 81.2% of MDR-TB patients in comparison with 41.6% of XDR-TB patients (21). These findings indicate that patients with XDR TB have higher probability of treatment failure and mortality (22,23).…”
Section: Clinical Coursementioning
confidence: 87%
“…In a retrospective study in Iran, successful outcome was observed in 81.2% of MDR-TB patients in comparison with 41.6% of XDR-TB patients (21). These findings indicate that patients with XDR TB have higher probability of treatment failure and mortality (22,23).…”
Section: Clinical Coursementioning
confidence: 87%
“…We were asked for a five-year review and after decades of immobility, we were very modest with our expectations. We even mentioned: 'It is unlikely that significant changes in the TB landscape will be witnessed in the next 5 years' [5]. We certainly acknowledge our misperceptions as more changes have occurred in last 5 years than in the preceding 40 ones.…”
Section: Main Changes In the Dr-tb Panorama In The Last 5 Yearsmentioning
confidence: 94%
“…In developing countries, however, the story was completely different; large numbers of DR-TB patients, limited availability of second-line drugs, and physicians were without experience on their use and toxicities [5].…”
Section: When Tb Became Appealing Againmentioning
confidence: 99%
See 1 more Smart Citation
“…Фактически имеются признаки развития эпидемиологического процесса, характе ризующиеся увеличенным риском вспышки в облас тях с высоким распространением ВИЧ инфекции вследствие высокой распространенности туберкуле за с МЛУ МБТ, однако пока данных о результатах лечения среди ВИЧ инфицированных пациентов с ШЛУ туберкулезом недостаточно. Доступные ис точники сообщают о чрезвычайно высоком уровне смертности и очень коротком времени выживания таких больных [17,18].…”
Section: обзорыunclassified